Analysis Driving Factor Implementation 5S in Manufacture (Case in PT. XYZ) - Valentin, Adelia Dwi; Soesilo, Rahman (Dinasti Publisher, 2025)
This research aims to analyze the driving factors of implementation with 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) in the Manufacturing industry. The method used in this research is a literature study from various sources of journals, books, and related publications. The results of the analysis can be identified five main factors that encourage the application of the 5S concept in the manufacturing industry are the first increase in production process efficiency. Second, there is an increase in employee discipline and work culture. Third, creating a safe and comfortable work environment. Fourth, increased productivity and competitiveness of the company due to efficiency and good work reputation. Fifth, there is a management commitment to continuous improvement with the support of resources and consistent evaluation. Effective implementation of the 5S concept is proven to benefit companies, especially manufacturers, by increasing efficiency, productivity, and a good work culture. These can be key factors that encourage the adoption of 5S in the manufacturing industry.